The effects of increasing SID lysine: ME ratio in growing and finishing pigs and the effect of copper and zinc supplementation in weanling pigs - Shelton, Nicholas William (Kansas State University, 2010)
Seven experiments were conducted to estimate the optimal standardized ileal digestible (SID) lysine:ME ratio for growing and finishing pigs. Experiment 1 determined an optimal SID lysine:ME ratio of 3.16 g/Mcal for 38 to 65 kg gilts. Experiment 2 reported an optimal level of 2.58 g SID lysine/Mcal ME for 55 to 80 kg gilts. Experiment 3 determined an optimal SID lysine:ME ratio of 2.55 g/Mcal for 85 to 110 kg gilts. In Exp. 4 and 5, growth rates were improved with porcine circovirus type 2 vaccine, with the optimal SID lysine:ME ratio for 38 to 65 kg gilts and barrows being 2.99 and 3.36 g SID lysine/Mcal ME, respectively. In Exp. 6 and 7, the optimal SID lysine:ME ratio was 1.86 and 2.61 g/Mcal for 102 to 125 kg gilts and 98 to 118 kg barrows, respectively. These trials indicate the optimal SID lysine:ME ratio for commercial growing and finishing pigs has increased compared with earlier estimates. Four experiments were also performed to determine the effect of copper (Cu) and zinc (Zn) supplementation on growth performance of weanling pigs. In Exp. 1, both 3,000 ppm Zn from zinc oxide (ZnO) and 150 ppm Cu from tri-basic copper chloride (TBCC) independently improved growth performance in weanling pigs due to increased feed intake. Similar results were observed in Exp. 2, where 3,000 ppm Zn from ZnO increased ADG and ADFI. Also, 125 ppm Cu from copper sulfate (CuSO4) increased growth rate due to enhanced feed intake, with Cu supplementation from TBCC offering intermediate results to CuSO4 and no Cu supplementation. For the first 28-d of Exp. 3, similar additive responses were observed to adding Cu and Zn to the diets of weanling pigs. However, from d 28 to 42 the combined use of Cu and Zn produced decreased performance compared each used singularly. Similarly in Exp.4, CuSO4 and ZnO improved growth performance, however the benefit was not additive. These trials showed growth promoting advantages to adding Cu and Zn to weanling diets, but additive responses were inconsistent.
Keywords: swine; lysine; copper; zinc; Agriculture, Animal Culture and Nutrition (0475)